Analisis Yuridis Atas Penggunaan Animasi Kartun Terkenal Sebagai Merek Di Indonesia (Studi Putusan Mahkamah Agung Nomor 1105 K/Pdt.Sus-HKI/2018) - Atika Putri Amira; Saidin Saidin; Keizerina Devi Azwar; Jelly Leviza (Iuris Studia: Jurnal Kajian Hukum, 2021)
Brand problems in Indonesia are dominated by infringement of well-known brands. One of them is the trademark dispute case between DC Comics and PT. Prosperous Marxing Fam. DC Comics, a comic book publisher from the United States, sued PT. Marxing Fam Makmur as a local chocolate wafer producer named Wafer Superman who is domiciled in Surabaya in the dispute over the Superman brand. DC Comics filed a lawsuit against PT. Marxing Fam Makmur stated that it is the owner of the Superman, Logo S, and Superman brands along with Paintings. The plaintiff asked the court to declare that the Superman trademark with registration numbers IDM000374438 and IDM000374439 on behalf of PT Marxing Fam Makmur had been registered in bad faith. The Plaintiff asks for the cancellation of the Superman brand. The problem in this research is how is the application of the principle of good faith related to the passing-off element of other brands even though they are not in the same class of goods; How is the application of the doctrine of brand dilution to disputes over rights to well-known marks in relation to restrictions on well-known marks; and How is the analysis of the judge's considerations related to the similarities in principle and/or overall as well as the application of the territorial principle to the DC Comics case as the owner of the famous Superman cartoon animation with the registration of the Superman icon by PT. Marxing Fam Makmur in Supreme Court Decision Number 1105 K/Pdt.Sus-HKI/2018 ? This type of research uses a normative juridical legal research method that is descriptive analytical, the source of the data used in this study is a secondary data source. The data were obtained by literature study. Literature research is carried out by reading books, journals, and laws and regulations that come from several literatures, documents, archives, applicable laws and regulations as well as the results of previous studies that are related and still relevant to the problem being studied. The application of the principle of good faith on the practice of passing off aims to guarantee consumers that the goods purchased come from the company that owns the brand. Legal protection for trademarks from passing off acts in the Indonesian legal constitution has not been specifically regulated in the trademark laws and regulations in Indonesia as well as for well-known brands, because passing off of a brand is commonly known in the common law system only for well-known brands that already have a reputation. Regarding passing off, it is contained in Article which implies its content in Article 21, Article 100, Law no. 20 of 2016. The application of the trademark dilution doctrine is not stated directly in Law Number 20 of 2016 concerning Marks and Geographical Indications. The arrangement is regulated in Article 21 paragraph (1 letter b, c) of Law no. 20 of 2016, Dilution in Law no. 20 of 2016, has not been explicitly regulated. The judge's interpretation in legal considerations in the case of DC Comics owner of the SUPERMAN Mark in the Supreme Court Decision Number 1105 K/Pdt.Sus-HKI/2018 is not correct, because it states that the plaintiff's claim cannot be accepted (niet ontvankelijk verklaard) so it has not been checked principally. Another legal effort was made by DC Comics on 27-05-2020, with Judge's decision No.29/Pdt.Sus/Merek/2020/PN.Niaga.Jkt.Pst, ending with DC Comics' lawsuit being granted against PT. Marxim Farm Makmur and stated that the Defendant's Mark had been registered on the basis of bad faith, as explained in Article 21 paragraph (3) of the Trademark Law.